Crossrail project: the impact of 4–18 Bishop's Bridge Road on the new Elizabeth line, London, UK. Issue 1 (19th February 2021) - Chodorowski, Adam; Ingram, Peter; Black, Mike
Abstract : This paper describes the interaction of the Crossrail project to deliver London's new Elizabeth line in the UK with a building situated directly over the machine-bored tunnels, close to Paddington station. The initial scheme called for the demolition of the existing building at 4–18 Bishop's Bridge Road, including extraction of existing piles, which would have had a considerable impact on the local area. Changes in the design of the Elizabeth line station at Paddington allowed a revised strategy to be considered, whereby the building could be kept, reducing construction costs to the project considerably. A combination of desk study and ground investigation works was used to identify the likely extent of the piling under the building, and to predict the risk of clashes with the tunnels. The results of analyses considering the impact of construction works on the building, and associated monitoring results are presented. The decision not to demolish produced numerous benefits aside from the reduction in cost, including a considerably reduced impact on those using the building and adjacent areas.